Entrepreneurial Mindset, Orientation, and Performance of University Students in Indonesia - Eddy Madiono, Sutanto; Evan, Lau; Andreas, Ezra (Research Center and Community Services (PPPM), 2021)
Entrepreneurship plays a vital role in determining the level of economic growth of a country. This study aims to explore the effect of entrepreneurial mindset on innovativeness, risktaking, competitive aggressiveness, autonomy, and proactiveness on entrepreneurial performance. Besides that, it also analyses the impact of these five factors on entrepreneurial performance. This research uses Partial Least Squares Structural Equation Modeling (PLSSEM) to analyze the data. The data were collected from 364 respondents, consisting of undergraduate students of management program from public universities in Surabaya, Indonesia. The results show that entrepreneurial mindset has a significant effect on innovativeness, risktaking, competitive aggressiveness, autonomy, and proactiveness. All of these factors, in turn, affect or enhance a positive and significant impact on the students’ entrepreneurial performance. It implies that the entrepreneurship education of public universities in Surabaya, Indonesia has succeeded in changing the students’ mindset and orientation. The government needs to increase entrepreneurship education centers and business incubator centers at the universities.